Application of geotube breakwater for muddy coastline protection in Peninsular Malaysia / Lee Siew Cheng - Lee , Siew Cheng (2018)
Muddy coastlines along the west coast of Peninsular Malaysia are experiencing severe degradation due to construction activities and clear-cutting of mangrove belts for socioeconomic development. Direct exposure of the muddy coast to storm surges, tides and waves will accelerate the coastline erosion. As a remedy for eroded coastal areas, revetments and dikes are normally construct along the eroding shorelines. Geotube breakwaters offer an alternative for coastal protection due to quick and ease of installation procedures, less impact to the environment and cost effective. However, published guidelines, technical publications and codes of practice for geotube breakwater are limited. Installation works were mainly based on engineers' experiences and judgement. There were cases where geotube breakwaters experienced sliding, overturning and excessive settlement due to inappropriate design process. This study was carried out to examine the application of geotube as a practical, viable and cost effective muddy coastal protection structure along the west coast of Peninsular Malaysia. Analyses were carried out to evaluate the advantages of utilizing the geotube breakwaters as a more versatile and environmentally friendly coastal protection option, especially on muddy coasts, as compared to other traditional coastal structures. The internal stability and external stability of geotube as coastal breakwater were studied. Optimum height, pumping pressure, maximum tension on geotube, structure deformation, displacement and settlement were analysed and evaluated, based on the wave conditions and geotechnical data from the study site in Sungai Haji Dorani (SHD), Selangor, Malaysia. Analyses of the external stabilities were carried out by using finite element analysis and the results were used to establish the factor of safety of the geotubes based on the geotechnical and geomorphological conditions in SHD. Based on this study, recommendation for the use of the waste material, quarry dust, as the filling material of geotube breakwaters was proposed. On the other hand, prediction of sediment activities with the presence of geotube breakwaters is important to ensure the optimum protection and nourishment effect. Hydrodynamic models were developed to simulate the changes in wave currents and directions before and after installation of geotube breakwaters. The predictions of sediment activities around geotube breakwaters were developed according to the outcomes of the analytical models and were compared with the field measurements to appraise the sturdiness of the results. Study showed that the geotube breakwaters are good alternatives for coastal protection, especially for muddy coastline, which have a softer and deformable foundation. The leeward regions sheltered by the geotubes breakwaters will provide a calm area for mangrove rehabilitation. In most of the tropical countries, matured mangroves act as natural barriers to minimize the dynamic effect of waves. Therefore, rehabilitation of mangroves along eroded coastlines is an important action to preserve the natural environment. The wave and geotechnical conditions used in this study represent the majority of the eroded mangrove mud coast along the west coast of Peninsular Malaysia. Thus, the methods applied in this study can be replicated to simulate or to predict the behaviours and effectiveness of geotubes breakwaters, with relatively similar coastal environment.